Amiodarone vs. metoprolol succinate in HFrEF complicated with persistent atrial fibrillation with rapid ventricular response: A prospective observational study - Liu, Yongrong; Hong, Yali (Frontiers in Cardiovascular Medicine, 2023)
Background β-blockers have been recommended for patients with heart failure (HF) and atrial fibrillation (AF), but studies have shown that β-blockers do not reduce all-cause mortality or cardiovascular mortality in patients with HF and AF. Objective To investigate the difference in efficacy between oral amiodarone and metoprolol succinate for patients with HF with reduced ejection fraction (HFrEF) and persistent atrial fibrillation (pAF) with rapid ventricular response (RVR). Methods Patients with HFrEF complicated with pAF with RVR treated in the People's Hospital of Chongqing Hechuan between March 2018 and March 2019 were enrolled in this prospective observational study. The primary outcomes were cardiovascular mortality and the first hospitalization for HF rate. The secondary outcomes were type B pro-brain natriuretic peptide (NT-proBNP) before/after treatment, left ventricular ejection fraction (LVEF) before/after treatment, average heart rate (AhR), and the rate of sinus rhythm after 1 year of follow-up. Results A total of 242 patients with HFrEF complicated with pAF with RVR were enrolled and divided into amiodarone + perindopril + spironolactone+ routine drug (amiodarone group, n = 121) and metoprolol succinate + perindopril + spironolactone +routine drug (metoprolol succinate group, n = 121) according to their treatment strategy. Cardiovascular mortality (4.9 vs. 12.4%, HR: 2.500, 95%CI: 1.002–6.237, P = 0.040) and first hospitalization for HF (52.9 vs. 67.8%, HR: 1.281, 95%CI: 1.033–1.589, P = 0.024) were significantly lower in the amiodarone group than in the metoprolol group. The mean ventricular rate in the amiodarone group was significantly lower than in the metoprolol group (64.5 ± 3.2 vs. 72.4 ± 4.2, P < 0.001). After 1 year of follow-up, the sinus rhythm rate was significantly higher in the amiodarone group than in the metoprolol group (38.8 vs. 7.4%, HR: 0.191, 95%CI: 0.098–0.374, P < 0.001). The difference in proBNP (3,914.88 vs. 2,558.07, P < 0.001) and LVEF (−6.89 vs. −0.98, P < 0.001) before and after treatment was significantly higher in the amiodarone group than in the metoprolol group. Conclusion In conclusion, in this prospective observational study, the amiodarone group had lower risk of cardiovascular death and the first hospitalization for HF than metoprolol in HFrEF and persistent atrial fibrillation (pAF) with RVR. The mechanism may be related to improved cardiac function, rhythm control and ventricular rate control. Registration number ChiCTR2200057816; Registered 7 March 2022–Retrospectively registered: http://www.medresman.org.cn/pub/cn/proj/projectshshow.aspx?proj=4222.